Bara, R. Finanzas Públicas y Decisiones Públicas: Un Enfoque de Economía Política - Martinez, Cintia (Estudios económicos, 2006)
Bara, R. Finanzas Públicas y Decisiones Públicas: Un Enfoque de Economía Política